Ecological Studies of Oryctes rhinoceros Larvae Controlled by Metarhizium anisopliae and Enthomopatogenic Nematodes - Indriyanti, D. R.; Rahmawati, R.; Priyono, B.; Slamet, M.; Huyop, F. Z. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
Oryctes rhinoceros L. (Coleoptera: Scarabaeidae) is a pest of coconut plant. Metarhizium anisopliae and Enthomopatogenic Nematodes are biological control agents. The purpose of this study was to determine the ecology of insect pests controlled by fungi Metarhizium anisopliae (MET), Enthomopatogenic Nematodes (NEP) and and the mixture of MET and NEP for controlling O. rhinoceros larvae on the field. M. anisopliae used was in the form of kaolin powder formulation (WP). The nematodes used were Heterorhabditios sp. Nematodes formulation was in the form of liquid with sponge medium contained 10 x 106 NEP in every pack. The study used Randomized Block Design with 3 types of treatment and 10 times repetition on 10 larvae. The result of six weeks treatment showed that the highest larval mortality was obtained from the treatment with the mixture of MET and NEP. Biological control using two biological agents (MET and NEP) is better than only MET or NEP. The benefit of research is for the recommendation of O. rhinoceros larvae control.